2019
DOI: 10.3390/ijms20122963
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Transcript Editing Across Mitogenomes of Early Land Plants Shows Novel and Familiar Trends

Abstract: RNA editing alters the identity of nucleotides in an RNA sequence so that the mature transcript differs from the template defined in the genome. This process has been observed in chloroplasts and mitochondria of both seed and early land plants. However, the frequency of RNA editing in plant mitochondria ranges from zero to thousands of editing sites. To date, analyses of RNA editing in mitochondria of early land plants have been conducted on a small number of genes or mitochondrial genomes of a single species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 73 publications
3
15
0
Order By: Relevance
“…The recent phylogenetic studies revealed the lower genetic diversity of Marchantiidae plastomes in comparison to evolutionarily younger Jungermannidae [9,12], but the reasons of slower evolution of the formers are not known. The lack or low level of RNA editing in comparison to other liverworts is another characteristic feature of Marchantiidae [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The recent phylogenetic studies revealed the lower genetic diversity of Marchantiidae plastomes in comparison to evolutionarily younger Jungermannidae [9,12], but the reasons of slower evolution of the formers are not known. The lack or low level of RNA editing in comparison to other liverworts is another characteristic feature of Marchantiidae [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate its organellar genome sequences, its chloroplast genome was sequenced previously (Kwon, Min, Xi, et al 2019). In addition, the mitochondrial genome of R. fluitans was also uncovered to understand RNA editing events on mitochondrial genomes of early land plants (Myszczy nski et al 2019). To understand intraspecific variations of mitochondrial genome of R. fluitans, we completed its mitochondrial genome sequences.…”
mentioning
confidence: 99%
“…Geneious R11 11.0.5 (Biomatters Ltd, Auckland, New Zealand) was used for annotation based on R. fluitans mitochondrial genome (NC_043906; Myszczyński et al. 2019 ).…”
mentioning
confidence: 99%
“…The reverse U-to-C RNA editing appears to be restricted to hornworts, some lycophytes, and ferns [44], but has not been confirmed in liverwort plastomes up to the date. The robust reverse editing was predicted for plastome of Gymnomitrion concinnatum [10], but in silico prediction tools seem to be incorrect in the case of U to C ending in the early land plants [2].…”
Section: Rna Editing In Organellar Genomesmentioning
confidence: 99%
“…Organellar genomes of early land plants are known from their stable structure and almost identical gene order present in all main evolutionary lineages [1][2][3][4][5], which include complex thalloids, simply thalloids, leafy and early divergent leafy liverworts from the order Treubiales and Haplomitriales. Despite the fact that the organellar genomes of model liverwort Marchantia polymorpha were among first sequenced plant plastomes [6] and mitogenomes [7], the number of complete genomes sequences was very limited, till the end of the second decade of XXI century, when several paper were published significantly expanding our knowledge about evolutionary dynamics of these molecules [2][3][4][5]. The current genomic resources comprise 61 mitogenomes and 59 plastomes complete sequences, but many liverwort families do not have their representatives.…”
Section: Introductionmentioning
confidence: 99%